Cognitive Conflict-Based Learning Materials Thermodynamics with Augmented Reality: Is It Practical in Physics Learning? - Devana; Fatni Mufit; Ratnawulan; Hayyu Yumna (Universitas Negeri Padang, 2025)
The problem of low conceptual understanding in physics learning is still often encountered, including in thermodynamics material. The use of technology such as Augmented Reality to support concept formation in physics education is still very limited. One solution that can be offered to overcome this problem is the development of cognitive conflict-based physics teaching materials using Augmented Reality in thermodynamics material. This study aims to analyze the practicality of cognitive conflict-based thermodynamics teaching materials. This study reports the results of a small group evaluation (practicality test) which is part of the Plomp model development stage. The research instrument used was a practicality questionnaire, which was analyzed using a percentage technique. The results of the practicality test showed an average score of 89.90%, which is included in the very practical category. Cognitive conflict-based thermodynamics teaching materials with Augmented Reality have proven to be practical for students to use, both in terms of ease of use, attractiveness, usefulness, and efficiency.